x-4forx=6

Simple and best practice solution for x-4forx=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-4forx=6 equation:


Simplifying
x + -4forx = 6

Reorder the terms:
-4forx + x = 6

Solving
-4forx + x = 6

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-4forx + x + -1x = 6 + -1x

Combine like terms: x + -1x = 0
-4forx + 0 = 6 + -1x
-4forx = 6 + -1x

Divide each side by '-4orx'.
f = -1.5o-1r-1x-1 + 0.25o-1r-1

Simplifying
f = -1.5o-1r-1x-1 + 0.25o-1r-1

Reorder the terms:
f = 0.25o-1r-1 + -1.5o-1r-1x-1

See similar equations:

| (x+6.5)(x-6.5)=0 | | -x^2+0+45=0 | | 5x-(-6)=46 | | X+2x+2=90 | | 3x-66=11x+134 | | 5x-(-7)=22 | | 30=(-13) | | -x^4+2x^2+35=0 | | 2(z-3)+4(2z-7)= | | 9w-17w=-16 | | 48y^2+120y+75=0 | | -65-(+42)= | | 5b+2b-6=15 | | (2x-1)(8-x)=0 | | 2x-8x-44=100 | | 5(3z-1)-2(z+1)=10(z+1) | | 2a-3a=7-6a+4-11 | | 14x^3-38x^2+44x-15=0 | | x-9=87 | | friends+fake= | | 15n=-15 | | X+38+38=90 | | -73+2x+7x=98 | | 4(u+3)-3(3u-7)= | | 3(x-2)(x-2)+3=6x-12 | | -8(t-5)-(t+3)=10 | | p+7=7-6p | | X+45+35.8=90 | | 5/8c-8=2 | | 92+78=180 | | Y=300x^2-12 | | -41-5x+7x=19 |

Equations solver categories